Religious education, postsecularity and neoliberalism - Fancourt, N (Palgrave Macmillan, 2020)
Fancourt considers how post-secular perspectives on religious education could intersect with current neoliberal modes of governance in education. He first outlines post-secular positions, both descriptive and normative, specifically exploring Jürgen Habermas’s arguments for religion in the public sphere; then he considers their implications for religious education. The effects of neoliberalism on education—and specifically religious education—in England, are outlined, before considering Milton Friedman’s theory of how capitalism and freedom are connected. Finally, the interrelationship between Habermas’s and Friedman’s theories is considered, and Fancourt hypothesises that confessional forms of religious education may thrive in a post-secular, neoliberal culture of governance, but pluralistic models may struggle to articulate their value.